Coleopteran-specific StaufenC functions like Drosophila melanogaster Loquacious-PD in dsRNA processing. - Kim, K.; Koo, J.; Yoon, J.S.; Reddy Palli, S. (RNA Biology., 2021)
In Drosophila melanogaster, PD isoform of the double-stranded RNA binding protein (dsRBP) Loquacious (Loqs-PD) facilitates dsRNA cleavage to siRNA by Dicer-2. StaufenC (StauC) was discovered as a coleopteran-specific dsRBP required for dsRNA processing in coleopteran insects. Here, we show that StauC is essential for the high RNAi efficiency observed in coleopterans. Knockdown of StauC but not the homologs of Loqs-PD and R2D2 evoked a long-lasting insensitivity to RNAi in the coleopteran cell line, Ledp-SL1. The dsRNA insensitivity induced by StauC knockdown could not be overcome merely by an increase in dose or time of exposure to dsRNA or expression of Loquacious or R2D2. Furthermore, StauC but not Loqs and R2D2 are required for processing of dsRNA into siRNA. StauC overexpression also partly restored the impaired RNAi caused by the knockdown of Loqs-PD in D. melanogaster Kc cells. However, StauC was unable to compensate for the loss-of-the function of Dcr-2 or R2D2. Overall, these data suggest that StauC functions like Lops-PD in processing dsRNA to siRNA.